The Effects Of Foreign Strategic Investors On Pricing Of Wealth Management Products Of Commercial Banks In China: Does Ownership Structure Matter? - Zhao, Hong; Zhao, Xueyan; Hou, Ning (Journal of Applied Business Research, 2017)
Allowing foreign strategic investors (FSIs) to hold minority stake in Chinese banks is very important for China’s banking. Based on data of 221 commercial banks from 2007 to 2015, we use difference in differences (DID) and propensity score matching (PSM) to investigate the effects of shareholding of FSIs on pricing of wealth management products (WMPs) for banks in China from single product view and every bank view. Besides, we further investigate the effects of bank ownership on above relationship. We find that FSIs’ acquisitions significantly enhance the expected rate of return of WMPs on both levels, however decrease the deviation of return of WMPs on single product level but have no evident effects on bank level. Finally, we find that the impact of acquisitions from foreign banks depend on Chinese banks’ ownership structure. Specifically, the effects of FSIs’ acquisitions on pricing of WMPs are positive for state-owned banks (SOBs), while are negative for city commercial banks.